Bone Incorporation of a Poly (L-Lactide-Co-D, L-Lactide) Internal Fixation Device in a Rat’s Tibia: Microtomographic, Confocal LASER, and Histomorphometric Analysis - Mamani-Valeriano, Harrisson Lucho [UNESP]; Silva, Nelson Padilha [UNESP]; Nímia, Heloisa Helena [UNESP]; Pereira-Silva, Maísa [UNESP]; Oliveira, Maria Eduarda de Freitas Santana [UNESP]; Rodrigues, Letícia Gabriella de Souza [UNESP]; Tavares, Paulo Matheus Honda [UNESP]; Hadad, Henrique [UNESP]; de Jesus, Laís Kawamata [UNESP]; Santos, Ana Flávia Piquera [UNESP]; Barbosa, Débora de Barros [UNESP]; Poli, Pier Paolo; et al. (MDPI, 2024)
This study evaluated the bone incorporation process of a screw-shaped internal fixation device made of poly (L-lactide-co-D, L-lactide) (PLDLLA). Thirty-two male Wistar rats received 32 fixation devices (2 mm × 6 mm) randomly assigned to either the right or left tibia and one implant in each animal. After 7, 14, 28, and 42 days, the rats were euthanized and the specimens were subjected to microtomographic computed tomography (microCT) and histomorphometric analyses to evaluate bone interface contact (BIC%) and new bone formation (NBF%) in cortical and cancellous bone areas. The animals euthanized on days 28 and 42 were treated with calcein and alizarin red, and confocal LASER microscopy was performed to determine the mineral apposition rate (MAR). Micro-CT revealed a higher percentage of bone volume (p < 0.006), trabecular separation (p < 0.001), and BIC in the cortical (p < 0.001) and cancellous (p = 0.003) areas at 28 and 42 days than at 7 and 14 days. The cortical NBF at 42 days was greater than that at 7 and 14 days (p = 0.022). No statistically significant differences were observed in cancellous NBF or MAR at 28 and 42 days. Based on these results, it can be seen that the PLDLLA internal fixation device is biocompatible and allows new bone formation around the screw thread.
Keywords: absorbable implants; bone regeneration; bone screws; osseointegration; X-ray microtomography